Best Answer

3x + y = 4

x + y = 0

solve for y

y = -3x +4

y = -x

substitute y = -x into y = -3x +4, so the result is: -x = -3x +4

solve for x

-1x = -3x +4

+3x +3x

2x = 4



x = 2

then plug the x-value into one of the bolded equations and solve for y.

I chose

y = -x

y = -(2)

y = -2

so the final answer is the ordered pair (2, -2)

User Avatar

Wiki User

โˆ™ 2012-05-16 16:11:28
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
1504 Reviews

Add your answer:

Earn +20 pts
Q: What is the solution for 3x plus y equals 4 and x plus y equals 0?
Write your answer...
Still have questions?
magnify glass
People also asked